CRM in handling Complaint: the Use of Consumer feedback Column in Raising Consumer Trust and Intention To Buy - Hamdan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2023)
The result states Citrus Hill Farm. perform a Customer Relationship Management (CRM) strategy in handling complaints through a customer data collection process, customer data analysis, data collection on complaints that can be detrimental. From the consumer's point of view, in-depth interviews were conducted with (1) product evaluation, (2) the price of submitting a complaint,(3) speed of handling complaints, (4) level of consumer satisfaction after filing a complaint. complaint. The results show that Citrus Hill maintains and increases consumer trust by using a Customer Relationship Management (CRM) strategy and handling any complaints quickly. Citrus Hill has product advantages in the form of plant seeds and other agricultural products as well as the ease of purchasing goods online. In terms of handling consumer complaints, Citrus Hill handles them quickly and satisfactorily so as to increase trust and purchase of Citrus Hill products